2003
DOI: 10.1105/tpc.008961
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Microtubule Dynamic Instability during Preprophase Band Formation Revealed by Yellow Fluorescent Protein–CLIP170 Microtubule Plus-End Labeling[W]

Abstract: At the onset of mitosis, plant cells form a microtubular preprophase band that defines the plane of cell division, but the mechanism of its formation remains a mystery. Here, we describe the use of mammalian yellow fluorescent protein-tagged CLIP170 to visualize the dynamic plus ends of plant microtubules in transfected cowpea protoplasts and in stably transformed and dividing tobacco Bright Yellow 2 cells. Using plus-end labeling, we observed dynamic instability in different microtubular conformations in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 68 publications
7
123
6
Order By: Relevance
“…First, a dynamic cytoskeleton is critical to allow the population of microtubules to explore many configurations. Therefore, the magnitude of β may reflect the activity of microtubule-associated proteins and kinases that take part in regulating microtubule dynamics (28). Interestingly, the cytoskeletal reorganization seen during preprophase was indeed shown to be supported by a dramatic increase in the dynamic instability of microtubules both on the cell cortex and in the cytoplasm (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a dynamic cytoskeleton is critical to allow the population of microtubules to explore many configurations. Therefore, the magnitude of β may reflect the activity of microtubule-associated proteins and kinases that take part in regulating microtubule dynamics (28). Interestingly, the cytoskeletal reorganization seen during preprophase was indeed shown to be supported by a dramatic increase in the dynamic instability of microtubules both on the cell cortex and in the cytoplasm (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the magnitude of β may reflect the activity of microtubule-associated proteins and kinases that take part in regulating microtubule dynamics (28). Interestingly, the cytoskeletal reorganization seen during preprophase was indeed shown to be supported by a dramatic increase in the dynamic instability of microtubules both on the cell cortex and in the cytoplasm (28,29). Another possible factor is the size of the tubulin pool that may affect the strength of the bias favoring short endoplasmic microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Their dynamics consist mainly of stochastic phases of polymerization and disassembly, a pattern of behavior known as dynamic instability (Mitchison and Kirschner, 1984), which can be defined in terms of growth, disassembly, the transition from growth to disassembly (catastrophe), and the transition from disassembly to growth (rescue; Hush et al, 1994;Dhonukshe and Gadella, 2003;Vos et al, 2003a). By changes in these dynamic instability parameters, cells rearrange the microtubular network and quickly respond to environmental and developmental stimuli (Desai and Mitchison, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase D (PLD) was found to bind microtubules and membranes in vivo, and PLD remained bound to the plasma membrane when microtubules were depolymerized with a calcium and cold treatment combination (Gardiner et al, 2001). Furthermore, treatment with an activator of PLD, n-butanol, released microtubules from the plasma membrane of tobacco (Nicotiana tabacum) BY-2 cells, suggesting a role for PLD in microtubule-plasma membrane attachment (Dhonukshe and Gadella, 2003). However, conflicting results were obtained in a later study, which found that cortical microtubule remained attached to the plasma membrane of tobacco BY-2 protoplasts after treatment with n-butanol (Hirase et al, 2006).…”
Section: Microtubule Interactions With the Plasma Membrane And Other mentioning
confidence: 99%